2019
DOI: 10.1017/s1473550419000296
|View full text |Cite
|
Sign up to set email alerts
|

The search for microbial Martian life and American Buddhist ethics

Abstract: Multiple searches hunt for extraterrestrial life, yet the ethics of such searches in terms of fossil and possible extant life on Mars have not been sufficiently delineated. In response, in this essay, I propose a tripartite ethic for searches for microbial Martian life that consists of default non-harm towards potential living beings, default non-harm to the habitats of potential living beings, but also responsible, restrained scientific harvesting of some microbes in limited transgression of these default non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Indeed, it is possible that the locus where Buddhism may have a significant contribution that is distinct from religions such as Christianity is in the formation of an ethical framework for dealing with life on other worlds. Capper's survey research on American Buddhists has shown that most American Buddhists affirm a no-harm approach to living beings, regardless of where those beings reside, as well as a no-harm ethic toward the ecosystems in which they live and support for a "scriptural ethical complex regarding the taking of resource lives [as] respectfully as possible" when it comes to scientific research on other worlds (Capper 2020). Buddhism, as Capper notes, is rather vague on the ethics of killing of lifeforms such as microbes and recognizes that it is impossible for humans to live without killing such organisms, and also that Buddhism in general tends to have high regard for human life (due to its ability to attain enlightenment) even while emphasizing the need to avoid killing other life forms as a way of respecting life in general.…”
Section: Implications For Space Explorationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is possible that the locus where Buddhism may have a significant contribution that is distinct from religions such as Christianity is in the formation of an ethical framework for dealing with life on other worlds. Capper's survey research on American Buddhists has shown that most American Buddhists affirm a no-harm approach to living beings, regardless of where those beings reside, as well as a no-harm ethic toward the ecosystems in which they live and support for a "scriptural ethical complex regarding the taking of resource lives [as] respectfully as possible" when it comes to scientific research on other worlds (Capper 2020). Buddhism, as Capper notes, is rather vague on the ethics of killing of lifeforms such as microbes and recognizes that it is impossible for humans to live without killing such organisms, and also that Buddhism in general tends to have high regard for human life (due to its ability to attain enlightenment) even while emphasizing the need to avoid killing other life forms as a way of respecting life in general.…”
Section: Implications For Space Explorationmentioning
confidence: 99%
“…This presents something of a dilemma in Buddhism, because it is recognized that humans, like other life forms, kill simply to survive, even while it is best from an ethical perspective for humans to avoid killing. Capper notes the comment of one of his research participants who asks who humans think they are to assume our lives are more valuable than those of microbes, and I think this idea captures a perspective on life that is found in several manifestations of Buddhism in Japan (Capper 2020).…”
Section: Implications For Space Explorationmentioning
confidence: 99%
See 1 more Smart Citation